Integrating local environmental issues into a problem-based learning e-book to improve students’ science competencies - Aisyah Zahrotul Islam; Fida Rachmadiarti; Sifak Indana (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
In the Society 5.0 era, a significant challenge for education is integrating science and technology to strengthen human resources by enhancing students’ science competencies. This study aims to develop a PBL e-book that integrates local environmental issues in Bojonegoro, East Java, and to describe its design, validity, and effectiveness in improving 10th-grade students’ science competencies. The e-book was developed using the ADDIE model, validated by experts before being applied in learning, and its effectiveness was measured using pre-test and post-test assessments. The study’s results showed that the e-book was highly valid with a score of 3.78, and effective as evidenced by the significant improvement in students’ science competencies between the pre-test and post-test results. This e-book not only supports contextual learning but also strengthens students’ abilities in scientific reasoning, problem-solving, and applying science concepts to real-life problems, reflecting the shift from science literacy to science competencies emphasized in the PISA 2025 science framework. This e-book serves as an innovative educational resource in this Society 5.0 era and supports the development of science competencies by integrating local environmental issues into biology learning.